Quo Vadis Quantum Mechanics? - Elitzur, Avshalom C.; Dolev, Shahar; Kolenda, Nancy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
For more than a century, quantum mechanics has served as a very powerful theory that has expanded physics and technology far beyond their classical limits, yet it has also produced some of the most difficult paradoxes known to the human mind. This book represents the combined efforts of sixteen of today's most eminent theoretical physicists to lay out future directions for quantum physics. The authors include Yakir Aharonov, Anton Zeilinger; the Nobel laureates Anthony Leggett and Geradus 't Hooft; Basil Hiley, Lee Smolin and Henry Stapp. Following a foreword by Roger Penrose, the individual chapters address questions such as quantum non-locality, the measurement problem, quantum insights into relativity, cosmology and thermodynamics, and the possible bearing of quantum phenomena on biology and consciousness.
What Is the Measurement Problem Anyway? Introductory Reflections on Quantum Puzzles -- Radically Quantum: Liberation and Purification from Classical Prejudice -- Quantum Physics as a Science of Information -- Quantum Theory Looks at Time Travel -- What Connects Different Interpretations of Quantum Mechanics? -- Is Quantum Mechanics the Whole Truth? -- Roundtable Discussion I: Physical Theories, Present and Future -- Determinism Beneath Quantum Mechanics -- Relational Quantum Mechanics -- Matrix Models as Non-Local Hidden Variables Theories -- Towards a General Operational and Realistic Framework for Quantum Mechanics and Relativity Theory -- What is Probability? -- On Hamilton-Jacobi Theory as a Classical Root of Quantum Theory -- Roundtable Discussion II: Quantum Mechanics and its Limits -- New Insight into Quantum Entanglement Using Weak Values -- Non-Commutative Quantum Geometry: A Reappraisal of the Bohm Approach to Quantum Theory -- Quantum Phenomena Within a New Theory of Time -- Event-Based Quantum Theory -- Quantum Phenomena of Biological Systems as Documented by Biophotonics -- Quantum Theory of the Human Person -- Roundtable Discussion III: Information and Observation.
Keywords: Physics; Philosophy; Gravitation; Quantum physics; Quantum computers; Spintronics; Physics; Quantum Physics; Philosophy, general; Quantum Information Technology, Spintronics; Classical and Quantum Gravitation, Relativity Theory; Electronic books